78 CT Imaging of Complex Calcified Peyronie's Disease. Issue 1 (1st April 2022) - Ericson, C; Haehn, D; Baird, B; Broderick, G
ABSTRACT: Introduction: Peyronie's Disease (PD) is a well described pathology affecting up to 5-10% of men. The presence and extent of penile calcifications is an important determinant in disease management. Calcifications have a variety of clinical presentations ranging from microcalcifications to calcified plaques. Calcified plaques were excluded from past Xiaflex clinical trials. Calcified plaques may necessitate plaque excision and grafting (E&G) sometimes combined with inflatable penile prosthesis (IPP) placement, which is more complex than plaque incision and grafting. Peyronie's Disease guidelines recommend color duplex Doppler ultrasound (CDDU) primarily to rule out Erectile Dysfunction. PD pathology such as corporal septal involvement, multifocal calcifications, and circumferential corporal calcification can be difficult to assess on penile ultrasound (PUS) due to acoustic shadowing and device limitations. We describe a series of patients in whom non-contrast CT scan was used to further define calcified or complicated pathology. Objective: To describe the role of non-contrast CT scan of the penis for anatomic evaluation and surgical planning in patients with complicated calcified Peyronie's disease. Methods: 23 male patients with a diagnosis of PD were evaluated by a single surgeon at a single academic institution between 2017 and 2021. All patients underwent color doppler ultrasound (CDDU) examination with artificial erection via intracavernosal alprostadil injection and were evaluated based on erectile function, plaque dimension, hourglass deformity, plaque septal involvement, and suspected calcification status. Patients with CDDU examination concerning for significant calcification or complexity proceeded to non-contrast CT scan for calcific confirmation and for 3-dimensional evaluation of their PD plaque prior to surgical discussion. Complexity was defined as concern for multifocal calcified plaques (>2), partial/complete circumferential corpus cavernosum involvement, or septal involvement. Results: All 23 patients had concerning findings on initial examination for calcified plaque. 9 of 23 (39.1%) patients had exam findings of an hourglass deformity. On CT evaluation, calcification was confirmed in 22 of 23 patients (95.7%). Plaque dimensions on CT scan ranged from 0.4 × 0.2 × 0.5 cm to 4.0 × 2.0 × 1.7 cm. Many of these measurements were approximations due to circumferential calcified plaque. This classic "gull-wing" appearance (Figure 1) was noted in 6 of 23 (26%) patients. 12 of 23 (52.2%) of patients had septal involvement on CT (Figure 2). 8 of 23 patients (34.8%) had significant multifocal disease (Figure 3). 8 of 23 patients (34.8%) decided to proceed with surgical correction via E&G (n = 3), IPP with E&G (n =1), or via IPP with manual remodeling via the Wilson technique (n = 4). Conclusions: Non-contrast penile CT scan for evaluation of calcified Peyronie's disease allows for increased accuracy of surgical planning especially when evaluating for multifocal disease, circumferential plaque and/or septal involvement. These elements are critical in being able to provide accurate surgical recommendations and post operative discussions. Disclosure: No